2009
DOI: 10.1042/bj20090278
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine degradation by the Group A streptococcal serine proteinase ScpC can be reconstituted in vitro and requires two separate domains

Abstract: Streptococcus pyogenes is one of the most common human pathogens and possesses diverse mechanisms to evade the human immune defence. One example of its immune evasion is the degradation of the chemokine IL (interleukin)-8 by ScpC, a serine proteinase that prevents the recruitment of neutrophils to an infection site. By applying the ANTIGENome technology and using human serum antibodies, we identified Spy0416, annotated as ScpC, as a prominent antigen that induces protective immune responses in animals. We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
(63 reference statements)
1
13
0
Order By: Relevance
“…In addition, Spy0416 was shown to mediate cleavage of IL-8, thereby impairing clearance from infected tissues and promoting resistance to neutrophil killing (30,66). We provided further evidence that this activity was also exhibited by the recombinant form of the Spy0416 protein and required the concerted actions of the enzymatic and ancillary domains of the large ScpC protein (21). These studies further strengthen the selection of Spy0416 as a candidate for a GAS vaccine.…”
Section: Figsupporting
confidence: 55%
“…In addition, Spy0416 was shown to mediate cleavage of IL-8, thereby impairing clearance from infected tissues and promoting resistance to neutrophil killing (30,66). We provided further evidence that this activity was also exhibited by the recombinant form of the Spy0416 protein and required the concerted actions of the enzymatic and ancillary domains of the large ScpC protein (21). These studies further strengthen the selection of Spy0416 as a candidate for a GAS vaccine.…”
Section: Figsupporting
confidence: 55%
“…Neutrophils are particularly responsive to CXC chemokines, comprising CXCL1 and CXCL2, which are murine homologues of human interleukin-8 (42). Convincing lines of evidence have demonstrated clear-cut formation of CXC chemokines in streptococcal infections (8,15), and we have recently observed that M1 protein triggers significant pulmonary formation of CXCL1 and CXCL2 (40). Thus, we next asked whether farnesyltransferase might regulate M1 protein-induced formation of CXC chemokines in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of chemokine levels appears to be an important pathogenic mechanism for invasive GAS. The bacterium encodes a protease, SpyCEP (PrtS, ScpC), capable of cleaving a number of human CXC chemokines in addition to murine CXCL1 and CXCL2; isogenic mutants lacking SpyCEP are less virulent than their wildtype counterparts (16,18,27,33). Continued work is needed to ascertain the specific role, if any, that SpyA-mediated avoidance of uptake plays in epithelial cell chemokine production.…”
Section: Discussionmentioning
confidence: 99%